Pemahaman Hadis Nabi Dalam Perspektif Psikologi Sosial: Hadis-Hadis Jihad - Ridwan Maulana Safii (Halaqatuna, 2025)
The study of hadith texts cannot stand alone, but must involve other disciplines, because social and religious problems are becoming increasingly complex, often involving not only theological-normative issues, but also social-practical and even political issues. Islamic teachings derived from the Qur'an and hadith need to engage in dialogue with cultural realities and developments of the times. Here, the paradigm of interdisciplinary connection becomes an inevitability, so that the analysis and conclusions drawn from hadith texts can be more dialectical and communicative in addressing the evolving social-religious issues faced by Muslim communities today. The interpretation of jihad is not solely synonymous with violence, war, or other terrifying things, but rather jihad is understood by the Prophet himself as being directed at his companions, according to their abilities. It is impossible for the Prophet (peace be upon him) to speak in a historical vacuum; any idea or concept, including the Prophet's sayings, is always based on historical problems, namely those related to the historical and cultural issues of that time. Through multidisciplinary approaches, it is hoped that a relatively more accurate, appreciative, and accommodative understanding of hadith can be achieved, one that is responsive to the changes and developments of the times. Therefore, in understanding a hadith, we should not only focus on the literal meaning of the text, but also consider the socio-cultural context of its time. Historically speaking, the contextual understanding of hadith that has developed through modern approaches such as historical, sociological, anthropological, geographical, and others began around the 1980s. Therefore, in addition to the social psychological approach, there are many other approaches that can be used to understand hadith.